Regioselective One‐pot Synthesis of New Unsymmetric Spiro Dihydrofurans in the Reaction of Mixed Two Different Cyclic β‐Dicarbonyl Compounds with BrCN and Aldehydes in the Presence of Et3N. Issue 3 (13th February 2015) - Noroozi Pesyan, Nader; Shokr, Alireza; Gharib, Ali; Tunç, Tuncay; Sahin, Ertan
Abstract: Crossed one‐pot reaction of mixed cyclic β‐dicarbonyl with various aldehydes in the presence of cyano gen bromide and triethylamine leads to the selective and efficient formation of crossed new unsymmetri cal spiro dihydrofurans at room temperature. The products were obtained in good to excellent yields. Structure elucidation was carried out by 1 H NMR, 13 C NMR, FT‐IR spectroscopy, Mass analyses and X‐ray crystallography technique. A proposed mechanism was discussed for the formation of products. Abstract : Crossed one‐pot reaction of mixed cyclic β‐dicarbonyl with various aldehydes in the presence of cyanogen bromide and triethylamine leads to the selective and efficient formation of crossed new unsymmetrical spiro dihydrofurans at room temperature.